Anesthetic complications in cesarean section - Borkar Patil, Vijaya P.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2018)
Background: Obstetric anesthetists need to face with the unique situation of providing anesthesia for caesarean sections, where they have to provide care for both the mother and the unborn baby. This study was performed in 100 women who underwent cesarean section, either elective or emergency to evaluate type of anesthesia, anesthetic complications and neonatal outcome. Methods: A retrospective study was conducted in 100 women with singleton pregnancy undergoing cesarean section in the department of Anesthesiology in collaboration with department of Obstetrics and gynecology at Dr PDMMC and Hospital, Amravati from January 2017 to March 2018. Detailed information regarding medical and obstetric history, intrapartum course, postpartum complications diagnosed before hospital discharge, and infant outcome were collected directly from maternal and infant charts. Other details like age of the patient, parity, type of cesarean section and type of anesthesia was noted. American Society of Anesthesiologists (ASA) scores and type of anesthesia was noted. Results: In our study, spinal anesthesia was given in 62 (62%) patients, epidural anesthesia was given in 20 (20%) patients, combined spinal-epidural anesthesia was given in 10 (10%) patients while general anesthesia was given in 8 (8%) patients. Anesthetic complications were less. About 10 (10%) patients had spinal headache, 4 (4%) patients had failed regional anesthesia, 2 (2%) patients had failed intubation while 2 (2%) patients had high spinal anesthesia. Babies of 96 (96%) patients had Apgar score at 5 minutes of more than 7 and babies of 4 (4%) patients had Apgar score at 5 minutes of less than 7. Only babies of 2 (2%) patients required intubation for resuscitation. Conclusions: This study provides strong evidence that the guidelines recommending regional block over GA for most cesarean section. It is beneficial for neonates as well as for mothers.